Studying the importance of localization of electronic commerce and its impact on foreign trade - معروف زمرده (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This study aims to study the role of electronic commerce to enhance it in a way that serves the activity of foreign trade operations, especially after its size began to increase rapidly and its emergence was accompanied by a fundamental change in its business environment. On the one hand, it is a tool of an intangible nature, and on the other hand, due to its unique character and its influential role in... Making commercial and economic activities more flexible and effective, thus activating small and medium enterprises, increasing competitiveness, speeding up completion of deals, and reducing costs and expenses that affect commercial operations. Its role in this has become clear in light of the anxious political conditions of some countries as well. Thus, it contributes to activating countries’ foreign trade and increasing the growth and flexibility of economic commercial activities.